2014
DOI: 10.1080/10494820.2014.881394
|View full text |Cite
|
Sign up to set email alerts
|

Why some teachers easily learn to use a new virtual learning environment: a technology acceptance perspective

Abstract: After a decade of Virtual Learning Environments (VLE) in higher education, many teachers still use only a minimum of its affordances. This study looked at how academic staff interacted with a new and unknown VLE in order to understand how technology acceptance and support materials influence (perceived and actual) task performance. In an experimental design, 36 participants were split into a control (online help) and experimental (instructor video) condition and completed five common teaching tasks in a new VL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(73 citation statements)
references
References 31 publications
3
51
0
8
Order By: Relevance
“…There is also a need to improve the frog VLE application itself to make it more user friendly. When users of a new VLE technology struggle with a particular functionality, easily accessible, clear and searchable support materials are important factors in accepting a VLE [5]. Research on the effectiveness of frogVLE and how to integrate it into teaching should be done.The findings must be shared to teachers to improve their teaching using frogVLE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also a need to improve the frog VLE application itself to make it more user friendly. When users of a new VLE technology struggle with a particular functionality, easily accessible, clear and searchable support materials are important factors in accepting a VLE [5]. Research on the effectiveness of frogVLE and how to integrate it into teaching should be done.The findings must be shared to teachers to improve their teaching using frogVLE.…”
Section: Discussionmentioning
confidence: 99%
“…It allows learning and teaching to occur anywhere in accordance with the learning of the 21st century, which is characteristically flexible and student-centered. A virtual learning environment helps teachers in managing student learning processes virtually [5]. The use of frogVLE creates an interactive learning environment that is capable of attracting students to science subjects.…”
Section: Introductionmentioning
confidence: 99%
“…As DL instructors struggled to find their rhythm in the new teaching environment, communication tools like Learning Management Systems (LMS), Course Management System (CMS) and other distance learning communication platforms were underutilized. Findings of Rienties, Giesbers, Lygo-Baker, Ma, and Rees, (2016) showed that majority of open distance learning instructors underutilized the communication tools provided for distance learning environment. Particular reference is to the use of virtual learning system (like FrogVLE).…”
Section: Malaysian Online Journal Of Educational Management (Mojem)mentioning
confidence: 99%
“…Mohiddin and Khalid (2014) state that 2% of the teachers use Frog VLE in learning. The majority of teachers only use VLE as a repository for students to acquire learning materials such as PowerPoint and reading lists (Rienties, Giesbers, Lygo-Baker, Ma, & Rees, 2016). Teachers' awareness of working in the 21st century and the lack of encouragement for teachers from the school to use technology in teaching in the classroom environment is also an issue (Uche & Chiemezie, 2016).…”
Section: B Issues and Challenges Of Using Frog Vles In Science Learningmentioning
confidence: 99%